An Efficient Elliptic Curve Cryptography-Based Secure Communication with Privacy Preserving for Autonomous Vehicle - Jiongen Xiao; Yi Liu; Yi Zou; Dacheng Li; Tao Leng (Journal of Advanced Transportation)
Internet of Vehicles can improve driving and riding experience, provide information needs, reduce environmental pollution, and improve transportation efficiency, thereby promoting the rapid development and application of intelligent transportation. Especially through the advantages of the rapidity of information exchange and the flexibility of real-time data processing, an autonomous vehicle can provide barrier-free, safe, and sustainable transportation. At present, the rapid progress of the Internet of Things has promoted the continuous development of a fully autonomous vehicle. However, the autonomous vehicle network uses wireless communication technology, and the openness of its communication channel makes the communication process vulnerable to various security attacks. Therefore, this paper proposes a practical and efficient secure communication in the autonomous vehicle. This scheme utilizes elliptic curve cryptography, which can protect the security of multiparty communication between vehicle, cloud server, and user with lower computation and communication overhead. This paper provides security verification for the scheme by using Scyther. An informal security analysis shows that this scheme can resist multiple attacks. Through a comparative analysis and performance evaluation of the schemes, we found that the scheme improves security while maintaining efficiency.